Effect of traumatic experiences on the addiction treatment process - Tuncer, Süheyla Betül; Şimşek, Zeynep (Journal of Dependence, 2022)
Objective: Substance addiction is one of the primary public health problems. The aim of this study was to investigate the effects of traumatic experiences of patients who were addicted and their families on addiction treatment process.Method: The sample of the study was composed of patients registered in the surveillance system of a District Health Directorate Addiction Unit and individuals and their families treated in the addiction clinic of a private hospital. Socio- Demographic Information Form, Traumatic Experiences List and Addiction Profile Index were applied to the participants.Results: Of the 82 people participated in the study, 52.4% were those living in the community, 47.6% were hospital sample. Participants were between the ages of 17 and 55 (median age is 28), 93% of them are male. 66.2% of individuals reported that they experienced a traumatic event before substance abuse, 86.2% during addiction and 33.8% during treatment. 85.7% of individuals with trauma experience reported that they did not receive any support for their traumatic experiences at any time during the treatment process, Only 14.3% received psychological support. A significant relationship was found between the quality of the relationship with family members the traumatic event exposure before addiction, and the traumatic experiences of caregiver during treatment and compliance with treatment.Conclusion: The findings of the study show that the frequency of traumatic experiences was high in substance-addicted individuals and their families, drug addiction treatments should be sensitive to trauma and the importance of developing family-supported psychosocial interventions.
Keywords: Substance addiction; traumatic experiences; addiction treatment